2011
DOI: 10.1016/j.bpj.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Nanopositioning: Structural Transitions of a Helicase-DNA Complex during ATP Hydrolysis

Abstract: The conformational states of Escherichia coli Rep helicase undergoing ATP hydrolysis while bound to a partial-duplex DNA (pdDNA) were studied using single-molecule FRET. Crystallographic studies showed that Rep bound to single-stranded DNA can exist in open and closed conformations that differ in the orientation of the 2B subdomain. FRET measurements between eight Rep mutants donor-labeled at different residues and pdDNA acceptor-labeled at the junction were conducted at each of the four nucleotide states. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…For Rep, the reduced processivity in vitro is due to the relative instability of the functional complex [120]. The open and closed conformational states of Rep helicase undergoing ATP hydrolysis while bound to DNA were studied using smFRET [151]. The biological significance of having multiple conformations might be to regulate the helicase activity.…”
Section: Single-molecule Methods Provide New Insights Into Sf1 Helicasesmentioning
confidence: 99%
See 1 more Smart Citation
“…For Rep, the reduced processivity in vitro is due to the relative instability of the functional complex [120]. The open and closed conformational states of Rep helicase undergoing ATP hydrolysis while bound to DNA were studied using smFRET [151]. The biological significance of having multiple conformations might be to regulate the helicase activity.…”
Section: Single-molecule Methods Provide New Insights Into Sf1 Helicasesmentioning
confidence: 99%
“…Although, earlier smFRET studies have suggested the closed form of Rep to be an inhibited form [167], later detailed studies revealed two distinct Rep-partial-duplex DNA conformations in the ATPγS and ADP states. Here the primary conformation is found to be similar to the closed form, and in the secondary conformation the duplex DNA and 2B domain are rotated relative to the rest of the protein [151]. The multiple conformations may provide a mechanism of regulation of helicase activity whereby interactions between Rep and other proteins may determine the relative conformational states of domain 2B.…”
Section: Protein–protein Interactions That Regulate Helicase Activitymentioning
confidence: 99%
“…Using FRET triangulation and the NPS, Andrecka et al determined the position of nascent RNA exiting RNA polymerase II,58d as well as the positions of the non‐template and upstream DNA in the same complex 58e. More recently, Balci et al used FRET triangulation and the NPS to probe the position of the ss/dsDNA junction in a helicase–DNA complex,58f and Treutlein et al determined the three‐dimensional architecture of an RNA polymerase II open promoter complex 58j. Using a slightly different approach, Sabir et al combined several smFRET measurements with MD simulations in determining the global structure of a four‐stranded DNA fork58k and, more recently, a three‐way DNA junction 58l…”
Section: Emerging Fret‐based Techniquesmentioning
confidence: 99%
“…Although, earlier smFRET studies have suggested the closed form of Rep to be an inhibited form [167], later detailed studies revealed two distinct Rep-partial-duplex DNA conformations in the ATP S and ADP states. Here the primary conformation is found to be similar to the closed form, and in the secondary conformation the duplex DNA and 2B domain are rotated relative to the rest of the protein [151]. The multiple conformations may provide a mechanism of regulation of helicase activity whereby interactions between Rep and other proteins may determine the relative conformational states of domain 2B.…”
Section: Protein-protein Interactions That Regulate Helicase Activitymentioning
confidence: 83%